The Phenomenon of Students’ Work Precarisation in an International Perspective. A Comparative Analysis of Work Experience of Polish, Czech and Slovak Academic Youth - Piotr Czakon (Communications of International Proceedings, 2020)
This paper presents some quantitative data from research among Polish, Czech and Slovak academic youth. One of the main aims of the project was to establish to what extend work experience of students from three adjacent countries has been marked by the burden of precariousness. To answer this question roughly one thousand students from selected seats of learning were surveyed in 2018. Based on the findings, six main categories of working students were distinguished. As it turns out, there are significant discrepancies between work evaluation and precarisation experience among employees representing different segments of the labour market. The awareness of those differences can be seen as a crucial premise for shaping state economic policies.
Keywords: precarious work; work values; academic youth.